Disease activity and damage in patients with primary Sjogren's syndrome: Prognostic value of salivary gland ultrasonography. - Vera Milic; Jelena Colic; Andja Cirkovic; Svetlana Stanojlovic; Nemanja Damjanov (PLoS ONE)
Objectives To assess the association between salivary ultrasonography (sUS) findings and disease activity and damage in patients with primary Sjogren's syndrome (pSS). We investigated the potential prognostic role of sUS as a tool in the assessment of disease activity. Methods In 303 pSS patients, disease activity was assessed by the European League Against Rheumatism (EULAR) Sjogren's Syndrome Disease Activity Index (ESSDAI), the EULAR Sjogren's Syndrome Patient Reported Index (ESSPRI), the Sjogren's Syndrome Disease Activity Index (SSDAI) and the Sjogren's Syndrome Disease Damage Index (SSDDI). The sUS parenchymal inhomogeneity (de Vita scoring system) was assessed in 303 pSS patients and 111 heathy controls. A receiver operating characteristic (ROC) curve was used to determine the cut-off value of the pathological sUS score. Logistic regression analysis was performed to assess risk factors for moderate and high disease activity. Results A pathological sUS score ≥ 2 was recorded in 271 (89.7%) patients and 8 (8.6%) healthy controls. Patients with moderate and high ESSDAI and SSDAI scores had significantly higher US activity in comparison to that of pSS patients with low disease activity (p = 0.006; p = 0.01, respectively). Additionally, pSS patients with moderate and high SSDDI scores had higher US activity (p = 0.031). Pathological sUS correlated with the glandular domain within the ESSDAI and SSDDI (p<0.001). The patients with a severe US score (5-6) had a 3.5 times greater chance of having moderate or high disease activity. The specificity of the severe de Vita sUS score for ESSDAI and SSDAI was 85.1% and 85.2%, respectively. In contrast, the sensitivity of a severe de Vita sUS score for ESSDAI was low, at 29.2%, while the sensitivity for the SSDAI was higher, 42.3%. In the analysis of disease activity, a de Vita score ≥ 5 could be used as a risk factor for moderate and high ESSDAI (p = 0.042) and SSDAI (p = 0.006). Conclusions Pathological salivary gland ultrasonography is associated with high disease activity and damage in pSS. Consequently, sUS abnormalities might be surrogate items for glandular domains in the assessment of disease activity and damage. Thus, ultrasonography of the salivary gland combined with clinical and serological markers might be part of the next prognostic and therapeutic algorithm in the near future.